RETRACTED: Microplastic pollution in intertidal sediments along the coastline of China. (August 2020) - Wang, Qing; Shan, Encui; Zhang, Bin; Teng, Jia; Wu, Di; Yang, Xin; Zhang, Chen; Zhang, Wenjing; Sun, Xiyan; Zhao, Jianmin
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editors-in-Chief and Authors. The corresponding author informed the journal that full permission had not been obtained to use all the samples documented in the study. The authors apologise for any inconvenience caused.